Vitamin B6 efficacy in the treatment of nonalcoholic fatty liver disease: an open-label, single-arm, single-center trial - Kobayashi, Takashi (J Clin Biochem Nutr, 2021)
Vitamin B6 is an important cofactor in fat metabolism and its deficiency has been correlated with nonalcoholic fatty liver disease. However, no study has investigated the efficacy of vitamin B6 supplementation in these patients. The aim of this open-label, single-arm, single-center study was to examine the therapeutic effect of vitamin B6 in patients with nonalcoholic fatty liver disease. Twenty-two patients with nonalcoholic fatty liver disease received vitamin B6 (90 mg/day) orally for 12 weeks. Clinical parameters were evaluated, and liver fat and fibrosis were quantified before and after treatment using magnetic resonance imaging-based proton density fat fraction and magnetic resonance elastography. Serum alanine aminotransferase levels, the primary endpoint, did not change significantly after vitamin B6 treatment (93.6 ± 46.9 to 93.9 ± 46.6, p = 0.976). On the other hand, magnetic resonance imaging-based proton density fat fraction, a parameter of hepatic lipid accumulation, was significantly reduced (18.7 ± 6.1 to 16.4 ± 6.4, p<0.001) despite no significant changes in body mass index, even in those not taking vitamin E (n = 17, 18.8 ± 6.9 to 16.7 ± 7.3, p = 0.0012). Vitamin B6 administration significantly ameliorated hepatic fat accumulation. As an inexpensive agent with few side effects, vitamin B6 could be a novel therapeutic agent for the treatment of nonalcoholic fatty liver disease.